THE EFFECT OF BIOSOLAR AND PERTAMINA DEX ON POWER PERFORMANCE, TORQUE AND DIESEL FUEL CONSUMPTION - Dandung Rudy Hartana; Harianto; Wahid Anwar (KURVATEK, 2023)
Initially, diesel motor fuel was only diesel, but now there are biodiesel and Pertamina Dex. In order to analyze the performance of a diesel engine, it is necessary to test it using Pertamina Dex and Biosolar. This study used an experimental method with four variations of engine speed, namely 1000 rpm, 2000 rpm, 2500 rpm, and 2500 rpm. The tool used in this research is a type 4JA1 diesel engine, the performance parameters of the diesel engine are power, torque, and specific fuel consumption. The results showed that engine performance using Pertamina Dex fuel was superior to that using biodiesel. The superiority of pertamina dex is the torque at 2500 rpm of 68.992 Nm, the power parameter has increased by 5.246%, while the specific fuel consumption of pertamina dex is 0.132% lower than biodiesel.